Apatinib-loaded CalliSpheres Beads for embolization in a rabbit VX2 liver tumor: characterization in vitro, pharmacokinetics and tumor response in vivo - Qin Shi; Yongning Lu; Songjiang Huang; Chen Zhou; Chongtu Yang; Jiacheng Liu; Jinqiang Ma; Bin Xiong (Taylor & Francis Group, 2020)
Apatinib mesylate is an oral antiangiogenic agent that can inhibit activation of vascular endothelial growth factor receptor-2 tyrosine kinase. However, its therapeutic use in liver cancer is restricted due to severe systemic toxicity. Our work aimed to construct apatinib-loaded CalliSpheres Beads (CBAPA) and investigate its application in transarterial chemoembolization (TACE) of liver cancer. The established stock solution containing 20, 40 or 60 mg apatinib were fully mixed with 100-300 μm CalliSpheres Beads (CB) for 2 hours, respectively. The highest loading efficiency at 30 min after combination in 20 mg group (maximum 70.7%). Further, apatinib can be steadily released from CBAPA in vitro release test. For pharmacokinetics and tumor response in vivo, sixty New Zealand white rabbits with VX2 liver tumor were assigned into four groups: sham (NS) group, apatinib solution alone (APA) group, CB group and CBAPA group. Apatinib was measured in plasma and liver tissue by high performance liquid chromatography-tandem mass spectrometry. Compared to APA group, the administration of apatinib by TACE with CBAPA resulted in low systemic concentration. In addition, intratumoural apatinib concentration was higher than adjacent hepatic parenchyma in the CBAPA group. Compared to other three groups, CBAPA group achieved lower tumor growth rate and improved survival time. In conclusion, these findings provide a basis for the potential application of apatinib-loaded CalliSpheres Beads in liver cancer.